Investigating the feasibility of electrical generation by using tidal method - Rosmin, Norzanah (Universiti Teknologi Malaysia, 2006)
A renewable energy is an energy sources that can be converted into electrical energy without worrying that it could have worn out. Generating electrical energy by using tidal effect is another source of a renewable energy without giving any negative impact on environment. The theory of tidal energy is that it cycle for 24 hours without stopping. Since tidal generation depends on height, then the most critical requirement for generating electrical energy by using tidal effect is the differences between low tide and high tide. To benefit the tidal as a reliable energy source, skims for generating are studied. A control system is designed to ensure that generating is up to maximum. This project is in purpose to state the true ability of generating electrical energy by using tidal effect. It is done by case study, model designing and simulation by using Visual Basic.